Effect of electroacupuncture on the MMP-2/9 pathway mediated blood-brain barrier permeability in mice with Parkinson's disease - Xiao-lei ZHANG; Meng-ni HU; Ya-nan LI; Yao WANG; Zhen RONG; Jun MA (World Journal of Acupuncture - Moxibustion)
ABSTRACT: Objective: To investigate the effects of electroacupuncture (EA) on the blood-brain barrier permeability and the regulation of matrix metalloproteinases (MMPs) in the mice with Parkinson's disease (PD). Methods: Forty-eight C57BL/6 mice were randomly assigned into the normal control (NC) group, the PD model (PD) group, the EA group and the EA + SB-3CT inhibitor group (EA + SB-3CT), with 12 mice in each group. In this experiment, the PD model was established by intragastric administration (IG) with rotenone for 4 wk in the PD group, EA group and EA+SB-3CT group. In the EA + SB-3CT group, 1 h after IG with rotenone, the mice were intraperitoneally injected with MMP-2/9 inhibitor, SB-3CT (25 mg/kg/d). After successfully modeled, in the EA group and EA + SB-3CT group, EA was conducted at “Fengfu (GV16)” and bilateral “Taichong (LR3)” and “Zusanli (ST36)”, at 1 mA and 2 Hz for 30 min each time, once a day, for consecutive 2 wk. The behavioral changes of the mice were observed in each group using the open field test, the level of tyrosine hydroxylase (TH) in the substantia nigra was determined by immunohistochemistry, the permeability of the blood-brain barrier was detected by Evans blue staining, and the protein expression of ZO-1, ocludin, claudin-1, MMP-2 and MMP-9 in the substantia nigra was detected by Western blotting. Results: Compared with the NC group, the behavioral scores increased (P < 0.05), while total time of locomotion, total distance and average speed were reduced (P < 0.05) in the PD group. The expression of TH in the substantia nigra decreased (P < 0.05), Evans blue level in the brain tissue increased (P < 0.05), and the protein expression of ZO-1, occludin and claudin-1 was lower (P < 0.05), whereas MMP-2 and MMP-9 expression was higher (P < 0.05) in the PD group. Compared with the PD group, behavioral scores decreased (P < 0.05), while the total time of locomotion, total distance and average speed increased (P < 0.05) in the EA group. Additionally, TH expression in the substantia nigra was elevated (P < 0.05), Evans blue level in the brain tissue was lower (P < 0.05), the protein expression of ZO-1, occludin and claudin-1 was up-regulated (P < 0.05), and MMP-2 and MMP-9 expression was down-regulated (P < 0.05) in the EA group. Compared with the EA group, Evans blue level was reduced (P < 0.05), the protein expression of ZO-1 and occludin was up-regulated (P < 0.05), and MMP-2 and MMP-9 expression was further down-regulated (P < 0.05) in the EA+SB-3CT group. Conclusion: EA can effectively ameliorate the motor dysfunction of PD mice, reduce the damage of dopaminergic neurons, and play a neuroprotective role. EA can effectively improve the blood–brain barrier permeability in PD mice by up-regulating the expression of tight junction proteins, ZO-1 and occludin, and down-regulating the expression of matrix metalloporteinases, MMP-2 and MMP-9. The neuroprotective role of EA may be obtained by improving the blood-brain barrier permeability mediated by MMP-2/9 pathway.